The Effect of Motivation and Work Environment on Job Satisfaction with an Impact on Employee Performance at PT. Bina Agramulya in Jakarta - Anggada Bayu Seta (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
This study aims to determine the effect of motivation and work environment on job satisfaction, impacting employee performance at PT. Bina Agramulya in Jakarta. The method used is explanatory research with a sample of 120 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study, motivation has a significant effect on job satisfaction by 40.4%, hypothesis testing obtained a significance of 0.000 <0.05. The work environment substantially impacted job satisfaction by 33.6%; hypothesis testing acquired a value of 0.000 <0.05. Motivation and work environment simultaneously significantly affect job satisfaction by 49.1%; hypothesis testing obtained a significance of 0.000 <0.05.